Ethical challenges in collecting pre-existing digital data for linguistic research - Dalmaijer Evi; Stommel Wyke; Pas Berber; Spooren Wilbert (Linguistics)
Pre-existing digital data are a valuable resource for linguistic research. Collecting these materials is often thought of as straightforward (“the data exist anyway”) and ethical dilemmas are given little consideration. In this article, we discuss microethical issues we encountered while collecting electronic text messages, photos, and videos posted on a digital platform and app during paramedical treatment. Since ethics and methods are intertwined, we discuss the various ethical and methodological aspects of collecting these sensitive digital data for our linguistic research project and reflect on the benefits and limitations of the choices we made during this process. We specifically highlight the interdependence of ethics with technology and discuss how this can be even more challenging when working in a specific institutional context characterized by different conceptions of ethics and technology. Our article highlights the importance of microethics complementing prevalent ethical guidelines. We show that when pre-existing digital data are available in non-public digital spheres, it is difficult for researchers to define in advance in ethical protocols or guidelines how the data can be collected and what ethical measures should be taken. We argue that ethical reflections should be at the center of research, including research on pre-existing digital data, guiding the decisions to be made at all stages.